2010
DOI: 10.1177/0093854809354961
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Psychiatric Disorder to Juvenile Recidivism

Abstract: Youths formally referred to probation authorities in Texas (791 male, 200 female) self-administered a structured diagnostic interview at intake. Data on demographics, offense characteristics, and reoffending (within 12 months of baseline) were extracted from official justice records. Logistic regression analyses were used to evaluate the contribution of diagnosis to recidivism, adjusting for demographic and offense characteristics. Baseline externalizing disorders were associated with increased recidivism risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
93
2
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 26 publications
(41 reference statements)
7
93
2
11
Order By: Relevance
“…Various studies have studied the association between psychiatric disorders and repeat offending [2125], but the specific disorders that predicted repeat offending differed among studies, and positive findings were reported with regard to SUDs [23], affective disorders [23], oppositional defiant disorder (ODD) [24], and CD [21, 25]. Some of these previous studies did not take into account comorbidity [24, 25], and this may have affected the results, considering the high rate of comorbid disorders.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have studied the association between psychiatric disorders and repeat offending [2125], but the specific disorders that predicted repeat offending differed among studies, and positive findings were reported with regard to SUDs [23], affective disorders [23], oppositional defiant disorder (ODD) [24], and CD [21, 25]. Some of these previous studies did not take into account comorbidity [24, 25], and this may have affected the results, considering the high rate of comorbid disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these previous studies did not take into account comorbidity [24, 25], and this may have affected the results, considering the high rate of comorbid disorders. McReynolds and colleagues reported that SUDs and DBDs, along with their comorbidity, predicted repeat offending [23]. Anxiety disorder predicted repeat offending only when it was comorbid with DBDs, and affective disorders were associated with repeat offending only when combined with SUDs in males [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As no empirical evidence for such speculation is available, such stereotyping must critically be examined. 6 An important, but sparse, body of studies [7][8][9][10][11] focuses on psychiatric disorders as predictors of recidivism in severe juvenile delinquents. These 5 studies suggest that psychiatric disorder is, to some extent, related to future offending.…”
mentioning
confidence: 99%
“…Reich (2014) reported that approximately half of his sample of youth placed in alternatives to the New York City justice system had been flagged with possible mental health concerns. Mental health problems have also been linked to higher rates of recidivism (McReynolds, Schwalbe, & Wasserman, 2010;Sullivan, Beysey, Hamilton, & Grillo, 2007). Even more pertinent, Sealock and Manasse (2012) observed that young offenders under stress and with poor coping skills are less likely to respond well to treatment.…”
Section: Discussionmentioning
confidence: 99%